Life Cycle Assessment (LCA) of Refused Derived Fuel and Biogas as Products as Option of Sleman Regency Municipal Solid Waste Management - Muhammad Abdul Ghony; Muhammad Mufti Azis; Titi Tiara Anasstasia (Indonesian Life Cycle Assessment Network (ILCAN))
Sustainable municipal waste management is a big challenge for cities in Indonesia such as Sleman Regency, in D.I.Yogyakarta. Waste to Energy (WtE) is one of the methods in municipal waste management. Energy recovery from municipal waste is expected to produce electricity and/or thermal energy and thereby may reduce the amount of waste transferred to landfills. This study aims to evaluate the environmental impact of two energy recovery scenarios of municipal solid waste management in Sleman Regency. Here, we investigated 3 option for MSW management: direct combustion of once sorted waste to produce energy (O-1) , an integrated combustion of inorganic waste through the formation of densified Refuse Derived Fuel (RDF) followed by energy production (O-2) and scenario which are including dRDF and biogas followed by energy production (O-3). The environmental impacts from both scenarios were computed with Life Cycle Assessment (LCA) simulation by using OpenLCA software. The impact assessment include global warming potential (GWP), acidification potential (AP), eutrophication potential (EP) and human toxicity potential (HTP). The LCA simulation results showed that the GWP value of O-1, O-2 and O-3 are 0,6741 kg CO2eq / kWh, 0. 65863 kg CO2eq / kWh, and 0,574 kg CO2eq/kWh respectively. The AP, EP and HTP values for O-3 are consistently lower than that of O-2 and O-3. Thus, the LCA simulation results showed that MSW conversion into dRDF and biogas as a part of WtE technology is more environmentally friendly than direct combustion of MSW to energy.